1987
DOI: 10.1111/j.1471-4159.1987.tb04105.x
|View full text |Cite
|
Sign up to set email alerts
|

Lead Enters Bovine Adrenal Medullary Cells Through Calcium Channels

Abstract: Agents that stimulate secretion also accelerate the rate of Pb uptake into adrenal medullary cells. For example, when cells are suspended in a medium containing 5 microM Pb2+, depolarization by 77 mM K increases the rate of Pb uptake from 12 +/- 1 to 47 +/- 5 mumol/(L cells X min). K-induced Pb uptake has an apparent Km for Pb2+ of 2.6 microM, and is antagonized by Ca2+ with a K0.5 of 1.4 mM. The Ca channel blocker D-600 inhibits Pb entry with a K0.5 of 0.4 microM. Pb uptake is also stimulated by the Ca channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(70 citation statements)
references
References 26 publications
8
61
1
Order By: Relevance
“…These channels are involved in the uptake of calcium by neurons and across the blood-brain barrier. These channels are also permeable to lead, and thus lead may stimulate its own uptake, into the brain and into neurons, by activating PKC (47). Subjects with high PKC activity in the presence of lead may have higher brain lead levels for a given blood lead level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These channels are involved in the uptake of calcium by neurons and across the blood-brain barrier. These channels are also permeable to lead, and thus lead may stimulate its own uptake, into the brain and into neurons, by activating PKC (47). Subjects with high PKC activity in the presence of lead may have higher brain lead levels for a given blood lead level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PKC activity could be a surrogate measure for brain lead levels. Ion channels and transporters that participate in cellular homeostasis, including voltage-dependent calcium channels, are regulated, in part, by PKC (47)(48)(49). These channels are involved in the uptake of calcium by neurons and across the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that Pb 2+ can be carried into cells via Ca 2+ channels Hinkle, 1997a, 1997b;Reuter, 1983;Simons, 1993;Simons and Pocock, 1987). Simons and Pocock (1987) used cells isolated from bovine adrenal medulla to demonstrate that Ca 2+ channels can mediate the uptake of Pb 2+ .…”
Section: Leadmentioning
confidence: 99%
“…Simons and Pocock (1987) used cells isolated from bovine adrenal medulla to demonstrate that Ca 2+ channels can mediate the uptake of Pb 2+ . Their data show that compounds, which depolarize the cell and subsequently open Ca 2+ channels, promote the uptake of Pb 2+ .…”
Section: Leadmentioning
confidence: 99%
“…Studies conducted in preparations of mammalian small intestine support the existence of saturable and nonsaturable pathways of lead transfer and suggest that lead can interact with transport mechanisms for calcium and iron (see Section 3.4.2, Absorption). Lead can enter cells through voltagegated L-type Ca 2+ channels in bovine adrenal medullary cells (Legare et al 1998;Simons and Pocock 1987;Tomsig and Suszkiw 1991) and through store-operated Ca 2+ channels in pituitary GH3, glial C3, human embyronic kidney, and bovine brain capillary endothelial cells (Kerper andHinkle 1997a, 1997b).…”
Section: Soft Tissuesmentioning
confidence: 99%